2021
DOI: 10.1097/01.aoa.0000796144.39697.5e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liposomal Bupivacaine and Conventional Local Anesthetic Agents in Regional Anesthesia: A Systematic Review

Abstract: 4. Warner LL, Hunter Guevara LR, et al. Creating a model to predict time intervals from induction of labor to induction of anesthesia and delivery to coordinate workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Liposomal bupivacaine local infiltration for TSA was associated with higher pain scores, greater opioid consumption and longer postanesthesia care unit stays, compared to single-injection ISB with ropivacaine [20 ▪▪ ]. Systematic review found little evidence that liposomal bupivacaine prolongs the duration of analgesia compared to conventional local anesthetics [21 ▪ ]. A combined systematic review and meta-analysis concluded that liposomal bupivacaine offered a small analgesic benefit that was not clinically relevant [22 ▪▪ ].…”
Section: Analgesic Pathway Componentsmentioning
confidence: 99%
“…Liposomal bupivacaine local infiltration for TSA was associated with higher pain scores, greater opioid consumption and longer postanesthesia care unit stays, compared to single-injection ISB with ropivacaine [20 ▪▪ ]. Systematic review found little evidence that liposomal bupivacaine prolongs the duration of analgesia compared to conventional local anesthetics [21 ▪ ]. A combined systematic review and meta-analysis concluded that liposomal bupivacaine offered a small analgesic benefit that was not clinically relevant [22 ▪▪ ].…”
Section: Analgesic Pathway Componentsmentioning
confidence: 99%